Enhancing Good Governance in Kelurahan Panggungharjo: An Organizational Psychology Case Study in a Community Setting - Siti Mulyani; Elli Nur Hayati (Journal of Educational, Health and Community Psychology, 2023)
Since 2014, Indonesia has enacted the Village Law, granting villages the authority to oversee the entire process of village development, aimed at fostering prosperous village communities. Despite this, research on achieving effective governance within village governments in Indonesia, through the combined lenses of Industrial Organizational Psychology (PIO) and Community Psychology, remains limited. To address this gap, our study investigates how the synergistic perspectives of PIO and Community Psychology contribute to our understanding of program strategies and governance within the Panggungharjo Village Government, with the ultimate goal of enhancing the welfare of its constituents. Employing a case study methodology, we analyze the data using Situational Analysis (SA). Data sources encompass in-depth interviews, focus group discussions (FGDs) involving key Panggungharjo village stakeholders, archival studies, and on-site observations. These diverse data are systematically coded and subjected to the principles of Situational Analysis (SA). This analytical approach not only seeks to uncover fundamental social processes but also illuminates the intricate relationships and interactions among the key elements operating within the field. The culmination of our findings takes the form of a "Relational Map" and a "Social World Arena," depicting the dynamic relationships and interactions observed in this study. Our research reveals that the success of the Panggungharjo Village Government in achieving good governance hinges on five strategic pillars and two governance reforms, blending principles of organizational development and community participation. This study offers valuable insights by demonstrating how the application of Industrial and Organizational Psychology in conjunction with community participation can pave the way for effective governance within village governments, ultimately benefiting the entire community.